2014
DOI: 10.7854/jpsk.2014.23.4.325
|View full text |Cite
|
Sign up to set email alerts
|

A Petrological Study of the Mudeungsan Tuff Focused on Cheonwangbong and Anyangsan

Abstract: Even though Mesozoic Mudeungsan tuff, located within Neungju Basin, has been named several rock names, it should be named as Mudeungsan tuff due to several evidences, such as fiamme, welded texture and rock fragments in the Mudeungsan tuff. Volcanic eruption boundary between the Cheonwangbong and Anyangsan areas is not clear, but petrochemical and mineral chemical evidences with different ages indicate clear petrological boundary between Cheonwangbong and Anyangsan. The Mudeungsan tuffs from Cheonwangbong and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Anyang due to fractional crystallization dominated by plagioclase (Jung et al, 2014). In the Late Cretaceous, micrographic granite and alkali feldspar granite were intruded into the Mudeungsan Tuff.…”
Section: Geologic Setting Geological Backgroundmentioning
confidence: 99%
“…Anyang due to fractional crystallization dominated by plagioclase (Jung et al, 2014). In the Late Cretaceous, micrographic granite and alkali feldspar granite were intruded into the Mudeungsan Tuff.…”
Section: Geologic Setting Geological Backgroundmentioning
confidence: 99%
“…In contrast, the zircon age data indicate that considerable amounts of sediments were transported from the southern Cretaceous volcaniclastic terrane to the central playa lake. Cretaceous volcanic activity in the Neungju Basin areas was generated from calk-alkaline magma, resulting in the deposition of felsic pyroclastic, andesitic to dacitic rocks, and rhyolite [58][59][60]. Although various types of volcanic rocks were formed, they are characterized by abundant plagioclase content.…”
Section: Contrasting Geochemical Signatures Of Tectonic Settings and Weathering Intensities In A Nonmarine Basinmentioning
confidence: 99%
“…Kim et al (2002) reported a welded structure and proposed the Mudeungsan columnar joint to be welded tuff. In addition, Jung et al (2014) suggested that Cheonwangbong and Anyangsan in the Mudeungsan region were formed from calc-alkaline magma in the continental subduction zone [4]. Lim et al (2015) reported formation ages in the range from 84.73 to 87.72 Ma through zircon U-Pb dating of Mudeungsan tuff samples [5].…”
Section: Introductionmentioning
confidence: 99%